A Study of the Effect of Styrene Concentration on the Molecular Weight of Polypropylene Produced Using Metallocene Catalysts - Rabagliati-Canessa, F; Rodriguez-Mercado, F (2011)
It has been observed in the production of polypropylene nanocomposites containing silicate materials that the molecular weight of the polymer used can have a significant effect on the final quality of the composites. The availability of polypropylene over a range of molecular weights with similar material properties (e.g. melting temperature and tacticity) is limited. Therefore, the ability to use a single catalyst system to generate polypropylene with a range of molecular weights is an attractive goal. In this contribution the use of styrene as a chain-terminating agent is explored, in order to produce materials with a range of molecular weights from a single catalyst system. It is found that the molecular weight of the polypropylene produced can be varied in the range from 120 000 to 9000 g mol-1 using the Me2Si(Ind)2ZrCl2/methylaluminoxane catalyst system. Copyright © 2011 Society of Chemical Industry The use of styrene to control the molecular weight of polypropylene produced using metallocene catalysts was explored. The concentration of styrene used directly influenced the molecular weight of the polymers produced. © 2011 Society of Chemical Industry.